Hydroxy-α-sanshool isolated from Zanthoxylum bungeanum Maxim. has antidiabetic effects on high-fat-fed and streptozotocin-treated mice via increasing glycogen synthesis by regulation of PI3K/Akt/GSK-3β/GS signaling - Zhang, Qing; Li, Ruo-Lan; Wang, Ling-Yu; Zhang, Ting; Qian, Die; Tang, Dan-Dan; He, Cheng-Xun; Wu, Chun-Jie; Ai, Li (Frontiers in Pharmacology, 2022)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disease characterized by hyperglycemia. The fruits of Zanthoxylum bungeanum Maxim. is a common spice and herbal medicine in China, and hydroxy-α-sanshool (HAS) is the most abundant amide in Z. bungeanum and reported to have significant hypoglycemic effects. The purpose of this study was to evaluate the ameliorative effects of HAS on T2DM and the potential mechanisms responsible for those effects. An acute toxicity test revealed the median lethal dose (LD50) of HAS is 73 mg/kg. C57BL/6 J mice were fed a high-fat diet and given an intraperitoneal injection of streptozotocin (STZ) to induce T2DM in mice to evaluate the hypoglycemic effects of HAS. The results showed that HAS significantly reduced fasting blood glucose, reduced pathological changes in the liver and pancreas, and increased liver glycogen content. In addition, glucosamine (GlcN)-induced HepG2 cells were used to establish an insulin resistance cell model and explore the molecular mechanisms of HAS activity. The results demonstrated that HAS significantly increases glucose uptake and glycogen synthesis in HepG2 cells and activates the PI3K/Akt pathway in GlcN-induced cells, as well as increases GSK-3β phosphorylation, suppresses phosphorylation of glycogen synthase (GS) and increases glycogen synthesis in liver cells. Furthermore, these effects of HAS were blocked by the PI3K inhibitor LY294002. The results of our study suggest that HAS reduces hepatic insulin resistance and increases hepatic glycogen synthesis by activating the PI3K/Akt/GSK-3β/GS signaling pathway.